1998
DOI: 10.1021/ma9805248
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium Melting Temperature of Syndiotactic Polypropylene

Abstract: Isothermal crystallizations from the melt of samples of syndiotactic polypropylene having different degrees of syndiotacticity have been performed. The thermal behavior and the structural features of the melt-crystallized samples have been analyzed by differential scanning calorimetry and X-ray diffraction. According to this analysis, less stereoregular samples, crystallized in disordered modifications of form I with defects implying local arrangements of the chains such as in form II, present recrystallizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(95 citation statements)
references
References 30 publications
(111 reference statements)
8
87
0
Order By: Relevance
“…However, the existence of absorption bands assigned to trans-planar conformations is also present. On the other hand, the occurrence of the bands which are related with the trans-planar conformation of sPP in the strained specimen is in agreement with the abovementioned studies, which report that crystalline phase transformation from the helical form I to the trans-planar form III take place with the application of strain [7,17,18,11,30,[31][32][33][34][35].…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…However, the existence of absorption bands assigned to trans-planar conformations is also present. On the other hand, the occurrence of the bands which are related with the trans-planar conformation of sPP in the strained specimen is in agreement with the abovementioned studies, which report that crystalline phase transformation from the helical form I to the trans-planar form III take place with the application of strain [7,17,18,11,30,[31][32][33][34][35].…”
Section: Resultssupporting
confidence: 90%
“…After cooling at room temperature, a film of 0.4 mm thick was obtained. According to several studies, the above-described preparation leads to the formation of a disordered modification of form I [33,58]. The temperature that was used in these experiments has been found that is high enough to obtain samples with high degree of crystallinity [59,60].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Especially, the melting of semicrystalline thermoplastic is a very complex process, which is influenced significantly by the crystallization conditions. Double or multiple melting behavior has been observed in many semicrystalline polymers such as polypropylene (PP) [23,24], polystyrene (PS) [25], poly(ether ether ketone) (PEEK) [26][27][28], poly(ethylene terephthalate) (PET) [29,30], poly(butylene-2,6-naphthalate) (PBN) [31], poly(trimethylene terephthalate) (PTT) [32], and some biodegradable aliphatic polyesters, e.g., poly(butylene succinate) and copolymers [33][34][35]. It is an important research subject in the field of polymer science to gain a basic understanding of the structural evolution related to thermal history (i.e., crystallization conditions) and to provide a deep insight into the crystallization and melting processes of semicrystalline polymers.…”
Section: Introductionmentioning
confidence: 99%